Individual support for economic and political changes: Evidence from transition countries, 1991-2004 - Riccardo Rovelli; Anzelika Zaiceva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Using a unique dataset for 14 transition economies, we propose a new measure for individual evaluations of transitional reforms, which we use to study, for the first time, the evolution of support for economic and political reforms from 1991 to 2004. We show that support for economic changes has been increasing over time after an initial drop, while support for political reforms has generally been higher. Support attitudes are lower among the old, less skilled, unemployed, poor, and those living in the CIS countries, especially during the 1990s. We also find evidence that transition-related hardship, opinions on the speed of reforms, political preferences and preferences towards redistribution, ideology and social capital matter. Finally, we show that individual preferences for state ownership and the quality of political institutions contribute mostly to explaining the lower levels of support in the CIS countries.
Keywords: O57; A13; P26; P36; 330